2005
DOI: 10.1084/jem.20041399
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid precursor dendritic cells facilitate allogeneic hematopoietic stem cell engraftment

Abstract: Bone marrow transplantation offers great promise for treating a number of disease states. However, the widespread application of this approach is dependent upon the development of less toxic methods to establish chimerism and avoid graft-versus-host disease (GVHD). CD8+/TCR− facilitating cells (FCs) have been shown to enhance engraftment of hematopoietic stem cells (HSCs) in allogeneic recipients without causing GVHD. In the present studies, we have identified the main subpopulation of FCs as plasmacytoid prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
184
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(191 citation statements)
references
References 52 publications
7
184
0
Order By: Relevance
“…The FC population has been characterized as having a subset of cells with a phenotype similar to p-preDC [20]. Previous reports have established that p-preDC do not express CD3ε and we have demonstrated that all cells positive for the plasmacytoid-DC marker PDCA-1 reside in the FC-CD3ε − subset [4].…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The FC population has been characterized as having a subset of cells with a phenotype similar to p-preDC [20]. Previous reports have established that p-preDC do not express CD3ε and we have demonstrated that all cells positive for the plasmacytoid-DC marker PDCA-1 reside in the FC-CD3ε − subset [4].…”
Section: Discussionsupporting
confidence: 49%
“…Results of the current study provide a potential solution to the dichotomy, as there is now evidence that the FC-CD3ε + subset directly induces FoxP3 + CD4 + CD25 + regulatory T cells suggesting that FC-CD3ε + cells have a role in the generation of these T cells following allogeneic SC plus FC transplantation in vivo. It is of interest that although both FC and p-preDC cocultures result in FoxP3 + CD4 + CD25 + regulatory T cell development in vitro, previous studies have demonstrated that p-preDC-mediated allogeneic SC engraftment was significantly less efficient than the FC population [20]. Therefore, not only does the FC-CD3ε + subset have a role in the facilitation of allogeneic SC engraftment without development of GVHD, a role for FC-CD3ε + cells in the induction of FoxP3 + CD4 + CD25 + regulatory T cells following allogeneic SC plus FC transplantation has been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DC subset secretes cytokines that may have skewed T cells away from the type 1 phenotype and induced a tolerant phenotype. 29,30 Following Adv-Flt3L treatment, splenic B and NK cell numbers were also increased with kinetics similar to the DCs, whereas T-cell numbers continued to rise through at least day 22 following Adv-Flt3L injection. Thus, at a dose of 1 Â 10 11 VPs, i.v.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, many anti-inflammatory or immunosuppressive drugs commonly used in transplantation, inhibit the maturation of DCs and potentiate their tolerogenicity (101). Plasmatoid DCs represent a recently characterized DC subset, the precursor of which can enhance allogeneic hematopoietic stem cell engraftment and promote donor-specific tolerance to skin grafts in mice (102). This ability to tolerize the indirect pathway may be particularly important for the prevention of chronic rejection.…”
Section: Peripheral Tolerancementioning
confidence: 99%